HERD AND MASTER MORALITY: A NIETZSCHEAN READING OF SIDHWA’S NOVEL THE BRIDE (1983) - Sabawoon Ubaid; Fatima Arshad; Saeed Ur Rahman; Wajid Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
Eminent thinkers, including Protagoras, Aristotle, Plato, Socrates, and Augustine, delineated moral philosophy into different patterns characterized by conflicting viewpoint. It was divided into two by Friedrich Nietzsche: master morality and slave morality. The characteristics of master morality are being strong, powerful, and high-minded in contrast to everyone else who is common, low-minded, and low. Nietzsche believed that a person with slave morality was someone whose humanity, patience, and obedience were viewed as lowly traits. Nietzsche dubbed the Ubermensch and compared him to a superman. Superman is a person who leads an independent life, possesses free will, and has a true feeling of value. These qualities benefit future generations and cover a positive route for them. Sidhwa exhibits these traits in a variety of roles in The Bride (1983). The study also demonstrates how morality affects society. The novel also describes the conditions that give rise to morality. The study is significant because this study of Nietzschean morality within The Bride (1983) offers an examination of contrasting mentalities and moral frameworks, enriching interdisciplinary understanding in philosophy and literature.